The progress of the microbe-gut-brain axis in sepsis-associated encephalopathy - He, Chen; Shi, Hui; Yu, Zhijie; Ma, Chunhan; Jiao, Zhiqiang; Li, Jin; Yang, Fei (Frontiers in Cellular and Infection Microbiology, 2025)
Sepsis-associated encephalopathy (SAE) is a diffuse brain dysfunction that is caused by sepsis without direct brain injury or central nervous system infection and is manifested as anxiety-like behavior and cognitive dysfunction. The microbiota-gut-brain axis, on the other hand, is a bidirectional communication network between the gut and the brain that modulates host behavior and cognitive function in many ways and is of central importance in the preservation of general health and homeostasis. Given the functional roles attributed to the microbiota-gut-brain axis (MGBA), contemporary research is progressively focused on elucidating relationships between SAE and alterations in compositional and quantitative intestinal microbiota profiles. This review consolidates interdisciplinary insights from immunology, microbiology, neuroendocrine signaling, and neural pathophysiology to evaluate the mechanistic contribution of the MGBA to the relief of cognitive impairments in SAE. By unifying these perspectives, with the aim of preventing or enhancing SAE-related neurological dysfunction for the formulation of MGBA-targeted therapeutic strategies.